A study on the recent challenges of the telecommunication sector in Bangladesh: Robi-Airtel merger - Abedin, Jainul (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.